Sudut Tenang Tanah Pasir-Lempung Pada Kondisi Runtuh - Anto Budi Listyawan; Renaningsih Renaningsih; Qunik Wiqoyah; Aditya Galih Pradana (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2020)
The soil layer is the combination of many types as well as the soil in the slope area. The soil in the slope is frequently a mixture of clay and sand. The stability of slope becomes dominantly an issue in the geotechnical engineering area. The collapse of the slope occurs because the gravity of external forces is exceeding the shear strength of the soil. The recent research develops the apparatus to determine the angle of repose of the sand-clay soil in the failure conditions. Sandy soil is taken from Beach and Merapi volcano. The clay added into the sand in the proportion of 0%, 5%, 10%, 15%, 20%, 25%, and 30%. The experiment is conducted by taking the height of the falling material of 15cm, 25cm, and 35 cm. Adding 0% to 15% clay brings the sand into SP Category, then adding 20%-30% makes the sand in the SC category. The Modulus if a fine grain of sand beach is smaller than Merapi sand. As the percentage of clay added to the sand higher, the difference of angle of repose of Merapi sand before and after failure is getting smaller, but it is not the case in Beach sand. The percentage of loss of volume of Merapi sand after failure is also going down as the portion of clay higher. The loss of volume of Beach sand added by clay is getting higher in failure condition..